Overview of the Judge's Forgiveness Concept Its Relation to The Legal Interests of Criminal Victims (RKUHP Concept Study) - Muhammad Rifai Yusuf; Briliyan Erna Wati; Muhammad Harun; Tri Nurhayati (Universitas Islam Negeri Walisongo Semarang, 2021)
Judge forgiveness (rechterlijk pardon) is a new concept in the Draft Criminal Code (RKUHP) which authorizes judges not to impose a crime even though the defendant is proven guilty with several provisions as a condition of forgiveness. The position of the victim becomes important to discuss regarding the existence of this concept because the defendant who should be responsible for his actions can be released from the charge, on the other hand, the victim as the object of the crime, in general, is the party who has suffered losses for his legal interests. So, this concept ideally accommodates the interests of the victim adequately as a condition for forgiveness. The urgency of the victim's position in the concept was rechterlijk pardon further elaborated through a study entitled